Critical views of education professionals regarding educational responses to the challenge of inclusion in Andalusian schools - Domingo Martos, Lorena; Pérez García, Mª Purificación; Domingo Segovia, Jesus (Education Policy Analysis Archives, 2019)
The article describes research findings on the perception of educational professionals regarding the current state of educational inclusion in Andalusia (Spain). This is a qualitative study that aimed to understand the opinion of both ordinary and support teachers on this subject. Using in-depth interviews, we gathered the opinion of 48 key respondentswith knowledge and proven professional practice in the field of educational responses to diversity. This study addresses this issue on the basis of both anecdotal experience and professional knowledge. Content analysis and critical discourse analysis were employed, using theNvivo 12 tools. These analyses revealed an outpouring of deep insights into the criticisms that are leveled at professional practice and the educational system. The results indicate that our education system is immersed in conformism with the belief that it has reached certain levels of schooling and integration, with a wide range of educational responses. The respondents reveal a critical, reflective, and proactive attitude towards this issue. They report the fact that in the current education system there are still pockets of exclusion and measures that favor inclusion, both of which produce exclusionary effects. They also hold the view that the system is more oriented towards rhetoric than inclusive practice.